Active epoxidation bipyridine-oxodiperoxotungstate catalysts - Hidalgo, Gabriel; Barozzino-Consiglio, Gabriella; Devillers, Michel; Gaigneaux, Eric M. (Molecular catalysis, 2022)
•Reaction of a Keggin anion with H2O2, followed by reaction with bipyridine, produces active epoxidation catalysts.•Addition of H3PO4 to the Keggin/H2O2 system, prior reaction with bipyridine, results in very active epoxidation catalysts.•All hybrids are composed of WO(O2)2 moieties decorated with small amounts of PWn (n= 1; 2; 3; 4) species. Herein, we report the preparation of four compounds obtained by the reaction of H3PW12O40/H3PO4/H2O2 with 2,2’-bpy (a-22) or 4,4’-bpy (a-44) and H3PW12O40/H2O2 with 2,2’-bpy (b-22) or 4,4’-bpy (b-44) for the catalytic epoxidation of cyclooctene with H2O2 under monophasic conditions. The anions of the four compounds are composed of oxodiperoxotungstate WO(O2)2 moieties and their overall anionic structures are less condensed than the pristine [PW12O40]3− polyoxometalate (PW12) precursor (Raman and IR spectroscopies). The peroxo anions and bipyridine interact in a way differing from one bpy isomer to the other. Isomer 4,4’-bpy interacts electrostatically with the peroxo species and 2,2’-bpy in a coordinative mode. Compounds synthesized with isomer 2,2’-bpy (a-22 and b-22) are more epoxidation-active than those containing 4,4’-bpy (a-44 and b-44). Compounds a-22 and b-22 share the same structure (PXRD), but a-22 exhibits substantially better catalytic activity. This superior catalytic efficiency is associated to the presence of phosphatooxoperoxotungstates PWn (n = 1; 2; 3; 4) species with high n value (namely PW4 > PW3 >> PW2) (31P NMR and Raman spectroscopies). The PWn species are produced before reaction with bipyridine as a result of the degradation of PW12 with H2O2 which, under the employed conditions, is complete after 30 min. In the aqueous solution, the PWn species are present in different concentrations and coexist in a fast-dynamic equilibrium. Under the operated catalytic conditions, our materials outperform the homogeneous benchmark catalyst of Venturello ((C6H13)4N+)3[PW4O24]3−) which shows poor activity. The most active a-22 and b-22 catalysts are partially dissolved in the liquid medium, but they precipitate as the epoxide builds in the reaction medium, allowing for potential catalyst separation and reuse. It is revealed that H2O2 is required not only to generate epoxidation activity, but to preserve the structure of the catalyst, since without it, the structural damaged appears irreversible. [Display omitted]